Leveduras probióticas no processo de translocação bacteriana em modelo experimental de obstrução intestinal em camundongos - Simone de Vasconcelos Generoso (2010)
There is evidence of the beneficial effects of probiotics in the intestinal mucosa protection and modulation of immune function, reducing bacterial translocation (BT). The aim of this study was to evaluate the effects of viable cells and nonviable probiotics, S. boulardii and S. cerevisiae (UFMG 905) in BT as well as its means of action in model intestinal obstruction (IO) in mice. We used 6 groups. Group I: Sham operated, Group II: intestinal obstruction (IO), Group III: IO+Sb and Group IV: IO+not viable Sb, Group V: IO+Sc, Group VI: IO+ not viable Sc. Animals in groups I and II were given for 10 days, gavage saline, and the animals in other groups received their treatments by gavage with probiotics. In 10 day all mice underwent the operation for the promotion of IO, except the Sham group. BT was determined by uptake of 99mTc-E.coli in the blood, lymph nodes, liver, spleen and lungs was significantly higher in group HI than in group Sham. Treatment with both yeasts, with both viable and non viable cells, reduced BT in the blood and all organs investigated, in addition to inhibiting the increase in intestinal permeability, as determined by uptake in the blood of 99mTc-DTPA. These data were confirmed by histology as intestinal histopathological lesions were more severe in the IO group compared to Sham and treated groups. Furthermore, treatments with probiotic were able to significantly increase the levels of IL-10 (p<0.05) and had the same effect on the levels of sIgA compared with the animals in group IO. The group IO+not viable Sc, was an exception since they were not observed significant increases in the levels of sIgA. In conclusion, treatments with both probiotics were able to prevent BT probably through immunomodulation and maintaining the integrity of the intestinal barrier. In the case of the yeast S. cerevisiae UFMG 905 some of its effects as stimulating the production of sIgA seem to depend on their viability.